2003
DOI: 10.2118/82412-pa
|View full text |Cite
|
Sign up to set email alerts
|

How Bit Profile and Gauges Affect Well Trajectory

Abstract: The importance of wellbore deviation is well recognized by the drilling industry. An analysis of a drilling system's directional behavior must include the directional characteristics of the drill bit. This paper presents a comprehensive analysis of the directional behavior of polycrystalline diamond compact (PDC) bits, including the effect of bit profile, gauge cutters, and gauge length. Numerical simulations as well as laboratory tests have been carried out to better understand the mechanisms of PDC bit devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Furthermore, it contradicts the classical static assumption which states that cutting forces do not depend on the cutting velocity [31]. Indeed, most existing cutting models are static [37,12,11,30,16].…”
Section: The Pure Torsional Approachmentioning
confidence: 98%
“…Furthermore, it contradicts the classical static assumption which states that cutting forces do not depend on the cutting velocity [31]. Indeed, most existing cutting models are static [37,12,11,30,16].…”
Section: The Pure Torsional Approachmentioning
confidence: 98%
“…There has been significant work in measuring side cutting of bits and stabilizers in the past. 5,7,9,23,36,43 This work has been capitalized on with an extensive amount of lab test data collected for the side cutting response of bits in the drilling laboratory under controlled conditions. An example of this for four different gauge pad designs is shown in Figure 14.…”
Section: Dynamic Modelmentioning
confidence: 99%
“…[1][2][3] Over the last 30 years several models have been published to predict DLS based on the bit and BHA. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The experimental and analytical work in this area has significantly improved the state of the art and this continues today.…”
Section: Introductionmentioning
confidence: 99%
“…Internally the Limiter Redesign Process was renamed Fast Drill The FDBM initiative was the continued evolution of the Fast Drill Process. Research and field trials confirmed that poor borehole quality [12][13][14][15][16][17][18] (enlargement, borehole patterns, hole out of round, ledges, etc.) contributed significantly to drilling dysfunction and inadequate hole cleaning.…”
mentioning
confidence: 89%